An analytical method for evaluating the quality of coke raw materials

Through the TG-DSC analysis method, the decomposition rate K of the coke raw material is calculated, and the ease of graphitization and the nature of the coke source are judged based on the curve characteristics, which solves the problems of long-term high-temperature treatment and difficulty in judging the nature of the coke source in the existing technology. Rapid evaluation and process guidance are achieved.

CN112649319BActive Publication Date: 2025-01-21NINGBO SHANSHAN NEW MATERIAL TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202010061544.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-01-16
Publication Date
2025-01-21
Estimated Expiration
2040-01-16

AI Technical Summary

Technical Problem

In the prior art, it is necessary to pass the long-term high-temperature graphitization of different coke raw materials to compare their difficulty of graphitization, and it is difficult to determine whether there are different coke sources in the coke raw materials.

Method used

The TG-DSC analysis method is used to calculate the decomposition rate K by measuring the TG curve and DSC curve, and judge the ease of graphitization of the coke raw material and the nature of the coke source based on the curve characteristics.

Benefits of technology

It can quickly and efficiently evaluate the difficulty of graphitization of different coke raw materials, and can quickly determine whether the coke raw materials are composed of coke sources with different properties, and guide the selection of graphitization process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112649319B_ABST
    Figure CN112649319B_ABST
Patent Text Reader

Abstract

The present invention discloses an analysis method for evaluating the quality of coke raw materials. The analysis method comprises the following steps: subjecting the coke raw materials to TG-DSC analysis, the heating rate of the TG-DSC analysis is 3°C / min to 10°C / min; wherein, the TG-DSC analysis measures a TG curve and a DSC curve; judging whether the coke raw materials are composed of coke sources of different properties according to the DSC curve; calculating the decomposition rate according to the data measured by the TG curve, thereby comparing the graphitization difficulty between different coke raw materials. The analysis method in the present invention can quickly and efficiently evaluate the graphitization difficulty of different coke raw materials, and is used to compare the capacity and compacted density of different coke raw materials after graphitization, which has guiding significance for the process selection of different coke raw materials in the graphitization treatment stage; and can quickly and accurately judge whether the coke raw materials are composed of coke sources of different properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an analytical method for evaluating the quality of coke raw materials. Background Art

[0002] Lithium-ion batteries have the advantages of good reliability, high safety, small size and light weight, and have been widely used in digital products, military products, electric vehicles and other fields. With the development of lithium-ion batteries, the market demand for graphite negative electrode materials has been greatly promoted.

[0003] In view of the differences in demand in market areas such as high energy density or high power density, it is critical to analyze whether different types of coke raw materials are composed of coke sources of different properties and whether they are easy to graphitize, and to compare the capacity and compaction density of graphite negative electrode materials made from different coke raw materials after graphitization, in order to quickly and effectively screen raw materials and guide project development. Therefore, it is urgent to provide an analytical method for quickly evaluating the quality of coke raw materials. Summary of the invention

[0004] In order to solve the defects in the prior art that different coke raw materials need to be subjected to long-term high-temperature graphitization treatment before their graphitization difficulty can be compared, and it is difficult to judge whether there are coke sources of different properties in the coke raw materials, the present invention provides an analysis method for evaluating the quality of coke raw materials. The analysis method in the present invention can quickly and efficiently evaluate the graphitization difficulty of different coke raw materials, and is used to compare the capacity and compaction density of different coke raw materials after graphitization, which has guiding significance for the process selection of different coke raw materials in the graphitization treatment stage; and can quickly judge whether the coke raw materials are composed of coke sources of different properties.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] An analytical method for evaluating the quality of coke raw materials comprises the following steps:

[0007] The coke raw material is subjected to TG-DSC analysis, wherein the heating rate of the TG-DSC analysis is 3°C / min to 10°C / min;

[0008] The volatile matter of the coke raw material is less than 2%;

[0009] The TG-DSC analysis measures a TG curve and a DSC curve;

[0010] The TG-DSC analysis is performed using method 1 or method 2:

[0011] The method 1 comprises the following steps:

[0012] When the coke raw materials are composed of coke sources of the same nature, the decomposition rate K=△m / (T2-T1)×100% is calculated according to the mass m, the initial decomposition temperature T1 and the final decomposition temperature T2 measured by the TG curve, and the graphitization difficulty of different coke raw materials is compared;

[0013] Wherein, the △m is the mass difference between the initial decomposition and the final decomposition of the coke raw material;

[0014] The second method comprises the following steps:

[0015] When the composition of the coke source of the coke raw material is unknown, judging whether the coke raw material is composed of coke sources of different properties according to the DSC curve; when the DSC curve presents n peaks and n≥2, the coke source of the coke raw material is composed of n coke sources of different properties; calculating the decomposition rate K of different coke raw materials according to K=△m / (T2-T1)×100% in method 1, and comparing the graphitization difficulty of different coke raw materials;

[0016] In the first and second methods, among different coke raw materials, when the decomposition rate K is smaller, the coke raw material is easier to graphitize.

[0017] In the present invention, the volatile matter may be the conventional concept of volatile matter in the art, for example, the content of the gas or liquid escaping from the coke after deducting the water content when the coke is heated in an airtight state at a temperature of 850°C to 950°C is equivalent to the mass loss after water correction when the coke is heated in an airtight state under specified conditions.

[0018] In the present invention, the coke raw material may be one or more of ordinary coke, needle coke, soft carbon and hard carbon; preferably ordinary coke or needle coke; more preferably needle coke.

[0019] Wherein, the ordinary coke may be conventional ordinary coke in the art.

[0020] The needle coke may be conventional needle coke in the art. Preferably, the needle coke has a silver-grey porous solid with a metallic luster. The needle coke has a structure with obvious flow texture, with large and few pores that are slightly elliptical, and particles with a large aspect ratio and a fibrous or needle-like texture.

[0021] The soft carbon may be conventional soft carbon in the art and is commercially available. Those skilled in the art should know that the soft carbon generally refers to a type of highly aromatic substance produced by pyrolysis and carbonization of fossil fuels and biomass under anaerobic conditions.

[0022] The hard carbon may be conventional hard carbon in the art and is commercially available. Those skilled in the art should know that the hard carbon generally refers to a type of carbon that is difficult to graphitize even at a high temperature of more than 2500°C.

[0023] In the present invention, the coke raw material may be coke powder.

[0024] The coke powder is preferably obtained by mechanically crushing lump coke raw materials using mechanical crushing equipment. After the mechanical crushing, a sieve can be used to remove large particles of coke powder visible to the naked eye. The mesh size of the sieve can be a conventional mesh size in the art, preferably 60 to 300 meshes, and more preferably 60 meshes.

[0025] Wherein, the D50 particle size of the coke powder may be 5 μm to 15 μm, preferably 9 to 10 μm.

[0026] In the first embodiment of the present invention, preferably, when the coke raw material is ordinary coke, when the initial decomposition temperature T1 of the coke raw material is less than 460° C., the graphitization degree of the coke raw material is less than 93.1%.

[0027] In the second embodiment of the present invention, the coke sources with different properties may be coke sources with different needle-like properties and / or graphitization difficulty.

[0028] Among them, those skilled in the art should know that the needle-likeness generally refers to the fibrous or needle-like structure of coke.

[0029] In the present invention, the coke raw material is preferably a heat-treated coke raw material.

[0030] In the present invention, the heat treatment may be a conventional heat treatment method in the art, preferably a calcination treatment.

[0031] The heating rate of the heat treatment may be a conventional heating rate in the art, preferably 2°C / min to 10°C / min, more preferably 3°C / min.

[0032] The temperature of the heat treatment may be a conventional temperature in the art, preferably 600°C to 1400°C, more preferably 900°C.

[0033] The heat treatment holding time may be a conventional holding time in the art, preferably 30 min to 200 min, more preferably 60 min.

[0034] The heat treatment equipment may be conventional heat treatment equipment in the art, preferably a tubular furnace, an oven or a carbonization furnace.

[0035] The heat treatment atmosphere may be nitrogen or argon.

[0036] In the present invention, the heat treatment preferably includes cooling.

[0037] The temperature after cooling can be below the initial decomposition temperature T1 of the coke raw material; preferably below 300°C; more preferably 25°C to 300°C.

[0038] In the present invention, the heating rate of the TG-DSC analysis may be 3°C to 5°C / min, preferably 5°C / min.

[0039] In the present invention, the temperature range of the TG-DSC analysis may be 25°C to 1000°C, preferably 300°C to 1000°C.

[0040] In the present invention, the atmosphere for TG-DSC analysis may be an atmosphere in which the coke raw material can be decomposed, preferably one or more atmospheres of air, oxygen, carbon dioxide and water vapor, more preferably an oxygen atmosphere or a carbon dioxide atmosphere, further preferably an oxygen atmosphere.

[0041] In the present invention, the TG-DSC analysis equipment may be a conventional TG-DSC analysis equipment in the art, preferably a synchronous thermal analyzer.

[0042] In the first method of the present invention, preferably, the difficulty of graphitization of different coke raw materials can be judged according to the gradient difference of the starting decomposition temperature T1 and the ending decomposition temperature T2 of different coke raw materials, and the easier the coke raw material is to graphitize, the higher the capacity and the greater the compaction density of the coke raw material after graphitization.

[0043] In the present invention, in order to verify the technical solution of the present invention, different coke raw materials can be graphitized according to conventional methods in the art, and their graphitization degrees can be tested. The coke raw materials after graphitization can be made into button batteries, and the capacity and compaction density of the button batteries can be tested.

[0044] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0045] The reagents and raw materials used in the present invention are commercially available.

[0046] The positive and progressive effects of the present invention are:

[0047] The analysis method of the present invention can quickly and efficiently evaluate the graphitization difficulty of different coke raw materials, and is used to compare the capacity and compaction density of different coke raw materials after graphitization, which has guiding significance for the process selection of different coke raw materials in the graphitization treatment stage; and can quickly determine whether the coke raw materials are composed of coke sources of different properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is the TG curve of the coke powder in Example 1 analyzed by TG-DSC.

[0049] Figure 2 This is the DSC curve of the coke raw material A in Example 2 analyzed by TG-DSC. DETAILED DESCRIPTION

[0050] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0051] In the following examples, the testing standards for the volatile matter of coke raw materials are all GB / T 7047-2006 Determination of the volatile matter content of pigment carbon black.

[0052] Example 1

[0053] The analysis method of three common coke qualities includes the following steps:

[0054] (1) Three different brands of ordinary coke raw materials were selected and crushed using a mechanical mill to obtain coke powders with a particle size D50 of 9 to 10 μm, which were marked as ordinary coke A, ordinary coke B, and ordinary coke C respectively;

[0055] (2) heating ordinary coke A, ordinary coke B and ordinary coke C in a tube furnace at a heating rate of 3°C / min to 900°C, maintaining the temperature for 60 min, and then cooling down. Collecting the calcined ordinary coke A, ordinary coke B and ordinary coke C, respectively, and marking them as ordinary coke A-900, ordinary coke B-900 and ordinary coke C-900; wherein the volatile matter of the coke powder after the heat treatment is less than 2%;

[0056] (3) Ordinary coke A-900, ordinary coke B-900, and ordinary coke C-900 were tested using a TG-DSC analysis device under an oxygen atmosphere. The temperature was raised from room temperature to 1000°C at a heating rate of 5°C / min, and TG-DSC curves were measured respectively.

[0057] Among them, there is a gradient difference between the starting decomposition temperature and the ending decomposition temperature of ordinary coke A-900, ordinary coke B-900 and ordinary coke C-900, which can be identified by temperature: ordinary coke A-900<ordinary coke B-900<ordinary coke C-900. From this, it can be seen that the thermal stability gradient of ordinary coke A, ordinary coke B and ordinary coke C after calcination is: ordinary coke A-900<ordinary coke B-900<ordinary coke C-900, and thus the difficulty of graphitization can be judged as: ordinary coke A<ordinary coke B<ordinary coke C.

[0058] To further verify the above conclusions, the ordinary coke A, ordinary coke B, and ordinary coke C were respectively subjected to high-temperature graphitization treatment using conventional methods in the art, their graphitization degrees were tested, and the ordinary coke A, ordinary coke B, and ordinary coke C after graphitization treatment were respectively made into button cells, and the capacities and compaction densities of the button cells were tested, as shown in Table 1.

[0059] Table 1

[0060]

[0061] It can be seen from this that when the coke raw materials are analyzed by TG-DSC, when the initial decomposition temperature is lower than 460 °C, the coke raw materials are subjected to the above-mentioned high-temperature graphitization treatment, and their graphitization degrees are tested. The graphitization degree is lower than 93.1%, and when they are made into button cells, the capacity is lower than 335.3 mAh / g, and the compaction density is lower than 1.57 g / cm 3 。

[0062] Example 2

[0063] The analysis methods for different coke raw material qualities include the following steps:

[0064] (1) Select three coke raw materials with different manufacturer grades, and use a mechanical mill to crush them to obtain coke powders with a particle size D50 of 9-10 μm, which are respectively marked as YD, JZ, and F66. Among them, YD, JZ, and F66 are needle cokes;

[0065] (2) YD, JZ, and F66 are respectively heated in a tube furnace at a heating rate of 3 °C / min to 900 °C, held for 60 min, then cooled and collected. The calcined YD, JZ, and F66 are respectively marked as YD-900, JZ-900, and F66-900; among them, the volatile content of the heat-treated coke powder is lower than 2%;

[0066] (3) The ordinary coke-900, YD-900, JZ-900, and F66-900 are detected using a TG-DSC analysis device in an oxygen atmosphere, heated from room temperature to 1000 °C at a heating rate of 5 °C / min, and TG-DSC curves are respectively measured, as Figure 1 。

[0067] It can be seen from this that there is a gradient difference between the initial decomposition temperature and the final decomposition temperature of YD-900, JZ-900, and F66-900. Identified by temperature: YD-900 < JZ-900 < F66-900. It can be seen from this that after the calcination treatment of YD, JZ, and F66, their thermal stability gradients are: YD-900 < JZ-900 < F66-900, so as to be able to judge the difficulty of graphitization as: YD < JZ < F66.

[0068] In order to further verify the above conclusions, conventional methods in the art were used to perform high-temperature graphitization treatment on YD, JZ, and F66, respectively, and their graphitization degrees were tested. The graphitized YD, JZ, and F66 were made into button batteries, respectively, and the capacity and compaction density of the button batteries were tested, as shown in Table 2.

[0069] The test method for graphitization degree is the conventional XRD graphitization degree analysis test method in the art; the conditions for button cell capacity test are active material: CMC: SBR: SP = 95.5: 1.5: 1.5: 1.5, surface density = 10 g / cm 2 .

[0070] Table 2

[0071]

[0072] The decomposition rate of the coke raw material K=△m / (T2-T1)×100%; the △m is the mass difference between the initial decomposition and the final decomposition of the coke raw material.

[0073] Example 3

[0074] Coke raw material A is composed of ordinary coke and needle coke uniformly mixed in a ratio of 10:100.

[0075] The analysis method for the quality of coke raw material A includes the following steps:

[0076] (1) crushing the coke raw material A by a mechanical mill to obtain coke powder with a D50 particle size of 9 to 10 μm;

[0077] (2) placing the coke raw material A in a tubular furnace, heating it to 900° C. at a heating rate of 3° C. / min, maintaining the temperature for 60 min, cooling it down, and collecting the calcined coke raw material A; wherein the volatile matter of the coke powder after the heat treatment is less than 2%;

[0078] (3) The calcined coke raw material A was tested using a TG-DSC analysis device in an oxygen atmosphere by heating from room temperature to 1000°C at a heating rate of 5°C / min. The DSC curve was measured as follows: Figure 2 ;

[0079] (4) Figure 2 As shown, the DSC curve of coke raw material A presents two peaks, which indicates that coke raw material A contains two coke sources with different properties; among them, the ordinary coke has an initial decomposition temperature of 472°C, while the needle coke has an initial decomposition temperature of 570°C.

[0080] It can be seen from the above test results that the analysis method for the quality of coke raw material A in Example 2 can accurately determine that coke raw material A is composed of two coke sources of different properties, further proving that the analysis method for evaluating the quality of coke raw materials of the present invention is fast and accurate.

[0081] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the embodiments, it is still possible for those skilled in the art to modify the schemes described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. However, any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An analytical method for evaluating the quality of coke raw materials, characterized in that: It includes the following steps: The coke raw material is subjected to TG-DSC analysis, wherein the heating rate of the TG-DSC analysis is 3°C / min to 10°C / min; The volatile matter of the coke raw material is less than 2%; the coke raw material is coke powder; the D50 particle size of the coke powder is 9-10 μm; The TG-DSC analysis measures a TG curve and a DSC curve; The TG-DSC analysis is performed using method 1 or method 2: The method 1 comprises the following steps: When the coke raw materials are composed of coke sources of the same nature, the decomposition rate K=△m / (T2-T1)×100% is calculated according to the mass m, the initial decomposition temperature T1 and the final decomposition temperature T2 measured by the TG curve, and the graphitization difficulty of different coke raw materials is compared; Wherein, the △m is the mass difference between the initial decomposition and the final decomposition of the coke raw material; The second method comprises the following steps: When the composition of the coke source of the coke raw material is unknown, judging whether the coke raw material is composed of coke sources with different graphitization difficulties according to the DSC curve; when the DSC curve presents n peaks and n≥2, the coke source of the coke raw material is composed of n coke sources with different graphitization difficulties; calculating the decomposition rate K of different coke raw materials according to K=△m / (T2-T1)×100% in method 1, and comparing the graphitization difficulties of different coke raw materials; In the first and second methods, among different coke raw materials, when the decomposition rate K is smaller, the coke raw material is easier to graphitize.

2. The analysis method according to claim 1, characterized in that The coke raw material is one or more of ordinary coke, needle coke, soft carbon precursor and hard carbon precursor.

3. The analysis method according to claim 2, characterized in that The coke raw material is ordinary coke or needle coke.

4. The analysis method according to claim 1, characterized in that In the first method, when the coke raw material is ordinary coke and the initial decomposition temperature T1 of the coke raw material is less than 500° C., the capacity of the button battery obtained after the graphitization treatment of the coke raw material is less than 350 mAh / g.

5. The analysis method according to claim 1, characterized in that The coke raw material is a coke raw material after heat treatment; The heat treatment is a calcination treatment; And / or, the heating rate of the heat treatment is 2°C / min to 10°C / min; And / or, the temperature of the heat treatment is 600° C. to 1400° C.; And / or, the heat treatment holding time is 30min to 200min; And / or, the heat treatment equipment is a tubular furnace, an oven or a carbonization furnace; And / or, the atmosphere of the heat treatment is nitrogen or argon.

6. The analysis method according to claim 5, characterized in that The heating rate of the heat treatment is 3°C / min; And / or, the temperature of the heat treatment is 900°C; And / or, the heat treatment holding time is 60 minutes.

7. The analysis method according to claim 6, characterized in that The heat treatment includes cooling down the temperature; The temperature after cooling is below the initial decomposition temperature T1 of the coke raw material.

8. The analysis method according to claim 7, characterized in that The temperature after cooling is below 300°C.

9. The analysis method according to claim 8, characterized in that The temperature after cooling is 25°C to 300°C.

10. The analysis method according to claim 1, characterized in that The heating rate of the TG-DSC analysis is 3°C to 5°C / min.

11. The analysis method according to claim 10, characterized in that The heating rate of the TG-DSC analysis was 5°C / min.

12. The analysis method according to claim 1, characterized in that The temperature range of the TG-DSC analysis is 25°C to 1000°C.

13. The analysis method according to claim 1, characterized in that The temperature range of the TG-DSC analysis is 300°C to 1000°C.

14. The analysis method according to claim 1, characterized in that The atmosphere analyzed by TG-DSC is an atmosphere in which the coke raw material can be decomposed; And / or, the equipment for TG-DSC analysis is a synchronous thermal analyzer.

15. The analysis method according to claim 14, characterized in that The atmosphere for the TG-DSC analysis is one or more of air, oxygen, carbon dioxide and water vapor.

16. The analysis method according to claim 15, characterized in that The atmosphere for the TG-DSC analysis is an oxygen atmosphere or a carbon dioxide atmosphere.

Citation Information

Patent Citations

  • Method for rapidly evaluating coke raw materials

    CN107764681A

  • Method for improving combustion performance of boiler by using coal quality combustion discrimination index

    CN110146545A

  • Evaluation and blending of coal for preparation of coke

    JP1999116968A